Platform interference in wireless systems : models, measurement, and mitigation - Slattery, Kevin (Newnes/Elsevier, 2008)
Intra-system EMC problems are becoming increasingly common in mobile devices, ranging from notebook PCs to cell phones, with RF/wireless capbilities. These issues range from minor annoyances to serious glitches which impede the functioning of the device. This book gives a thourough review of electromagnetic theory (including Maxwell's equations), discusses possible sources and causes of intra-system interference, shows to use models and analysis to discover potential sources of intra-system EMC in a design, how to use appropriate tests and measurements to detect intra-system EMC problems, and finally extensively discusses measures to mitigate or totally eliminate intra-system EMC problems. With more and more mobile devices incorporating wirless capability (often with multiple wireless systems, such as Bluetooth and WiFi), this book should be part of the reference shelf of every RF/wireless engineer and mobile device designer. *Throughouly describes sources of intra-system interference in RF/wireless devices and how to minimize them for maximum device performance *Gives proven techniques for interference mitigation, ranging from the simple (component placement and cable routing) to the advanced (such as the use of shielding and signal absorption materials) *Discusses modeling and analysis methods to predict likely sources of intras-system EMC *Explains test and measurement techniques to detect intra-system EMC problems.
Keywords: Wireless communication systems.; elektronické knihy; electronic books